PERAN CAMAT DALAM PROGRAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN CILEDUG KOTA TANGERANG - Suhanda . (Prima Center Indonesia, 2017)
The purpose of this study is to identify and explai about role and effort of theHead of District by the implementing of Remodelling the House Unihabitable in the Tajur and Paninggilan Disrict area of Tangerang City. The theory used are government organization, the concept of society development, leadership concept and the role of concept. The research method used descriptve qualitative method by using observation and interview techniques. Results of this reseacrh knowed by successfull of the Head of Ciledug District with the capacity of its ability to provide guidance, assigement and coordination to the implementing of Remodelling of Housing Uninhabitable in the Tajur and Paninggilan Village as the scope of activities of the human development, and establish institution that could including the active partisipation of the Village together with RW and RT, and Society of Self-Reliance Agency (BKM) in each Village and with the whole society has shown the Head-District role as a policy, as a tools of communication, and as a strategy. These three roles are performed with the principle of solidarity, openess, deliberation and participation, so it can get problem solving through socialization to provide an explanation for the problem of complaints from the local society on priority beneficiaries, as well as budget constraints Tangerang Government delegated as an authority in its implementation to the Ciledug Head of District.